PENERAPAN MODEL PEMBELAJARAN TEAM QUIZ UNTUK MENINGKATKAN BERPIKIR KRITIS DAN PRESTASI BELAJAR SISWA (Studi Mata Pelajaran Mata Pelajaran PAI Dan Budi Pekerti Siawa Kelas X SMK Negeri 2 Lahat) - Tillawari Tillawari (UNIB Press, 2020)
This study aimed to describe the application of the team quiz learning model and describe the effectiveness of the application of the Team Quiz learner model to improve critical thinking thinking skills and learning achievement of Islamic religious education in class X TKJ SMK Negeri 2 Lahat. The research method used was Classroom Action Research (CAR) and quasi experimental. The subject of the research was students of class X TKJ 1 semester one of the2019/2020 school year SMK Negeri 2 Lahat. For quasi experimental samples are class X TKJ 3 .and X TKJ 2. The number of students for the PTK class is 27 students for the experimental class totalling 27 students, and for the control class there are 27 students. Data collection methods in this study used observation sheets for the implementation of Team Quiz learning, observation sheets for critical thinking skills, and learning achievement tests. Data analysis uses tests that consist of different tests between cycles and different tests of two unrelated samples. The results of the study show that the application of the Team Quiz learning model can improve critical thinking skills, and effectively improve student achievement in Islamic Religious Education and Characteristics